An update on excess mortality in the second year of the COVID-19 pandemic in Germany - Giacomo De~Nicola; Göran Kauermann (AStA Wirtschafts- und Sozialstatistisches Archiv, 2022)
In this short note, we apply the method of De Nicola et al. ( 1 ) to the most recent available data, thereby providing up-to-date estimates of all-cause excess mortality in Germany for 2021. The analysis reveals a preliminary excess mortality of approximately 2.3% for the calendar year considered. The excess is mainly driven by significantly higher excess mortality in the 60-79 age group. – – In diesem kurzen Beitrag wenden wir die Methode von De Nicola et al. ( 1 ) auf die neuesten verfügbaren Daten an und zeigen aktuelle Schätzungen der Gesamt-Übersterblichkeit in Deutschland für das Jahr 2021. Die Analyse zeigt eine vorläufige Übersterblichkeit von etwa 2,3% für das betrachtete Kalenderjahr. Dieser Wert ist hauptsächlich auf eine deutlich höhere Übersterblichkeit in der Altersgruppe der 60-79-Jährigen zurückzuführen.
Keywords: 510; COVID-19; Excess mortality; Expected mortality; Standardized mortality rate; Übersterblichkeit; Erwartete Sterblichkeit; Standardisierte Mortalitätsrate